PENGARUH INDEKS PEMBANGUNAN MANUSIA, TINGKAT UPAH MINIMUM, DAN TINGKAT PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2022 - Mukaromah, Laila; Hanifatuzzahra, Zakia; Nasrullah, Ade; Latifah, Tiara Mukti; Purwaningsih, Vitriyani Tri; Suparta, I Wayan (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2023)
Indonesia according to data from the minister of economy that in the fourth quarter of 2022 economic growth has grown by 5.01% (yoy). In the full year, Indonesia's economic growth throughout 2022 was recorded to have experienced impressive growth of 5.31%. This figure exceeded the target set by the Government of Indonesia, which was 5.2%, and again reached the level of 5% as before the COVID-19 pandemic. Based on these problems, it is necessary to know what factors affect the economic growth of each province in Indonesia in 2022. The purpose of this study is to find out what factors affect the economic growth rate in Indonesia in 2022. A regression analysis of the effect of HDI, UMP and unemployment rate on the growth rate of GDP at constant prices in each province in Indonesia was carried out in 2022. This study used a quantitative approach and Cross Section data type with secondary data obtained from the BPS Website. The method used is Ordinary Least Squared. The conclusion obtained is that HDI, minimum wage and unemployment rate do not have a significant effect on economic growth, but the minimum wage can have a positive effect on the economic growth of each province in Indonesia in 2022. With Test F showing that in 2022, HDI, UMP and unemployment rate simultaneously (together) have no significant effect on economic growth. The variation of HDI, UMP, and unemployment rate, according to the coefficient of determination (R-Square), is only able to contribute 4.31% to Indonesia's economic growth in 2022